2003
DOI: 10.1007/s00705-003-0118-5
|View full text |Cite
|
Sign up to set email alerts
|

Screening for T cell-eliciting proteins of Japanese encephalitis virus in a healthy JE-endemic human cohort using recombinant baculovirus-infected insect cell preparations

Abstract: The analysis of cell-mediated immune responses in virus-exposed but healthy individuals may contribute to define the features of the T cell response associated with resistance. We report, for the first time, on adaptive T cell responses to 5 largest of the 10 proteins that together constitute 76% of the coding potential of the Japanese encephalitis virus (JEV) genome in a naturally exposed healthy JE-immune human cohort. Fixed and sonified whole cell preparations of insect cells individually expressing recombi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
20
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 33 publications
3
20
0
Order By: Relevance
“…Modified live vaccines, such as CP-WN and WN-FV, should be capable of the induction of cell-mediated immunity in addition to humoral immunity. The importance of cellmediated immunity (T-helper response and cytotoxic T cells) and memory T cells in the protection against WNV and other related flaviviruses has been demonstrated in experimental murine studies (7,24) and field studies characterizing populations among whom flavivirus is endemic (Japanese encephalitis and dengue fever) (13,27). Characterization of the protective immune responses to equine WNV vaccines has not been studied for horses due to the limitations of the previous mosquito and needle inoculation challenge models combined with the limited availability of equine-specific immunologic reagents.…”
Section: Discussionmentioning
confidence: 99%
“…Modified live vaccines, such as CP-WN and WN-FV, should be capable of the induction of cell-mediated immunity in addition to humoral immunity. The importance of cellmediated immunity (T-helper response and cytotoxic T cells) and memory T cells in the protection against WNV and other related flaviviruses has been demonstrated in experimental murine studies (7,24) and field studies characterizing populations among whom flavivirus is endemic (Japanese encephalitis and dengue fever) (13,27). Characterization of the protective immune responses to equine WNV vaccines has not been studied for horses due to the limitations of the previous mosquito and needle inoculation challenge models combined with the limited availability of equine-specific immunologic reagents.…”
Section: Discussionmentioning
confidence: 99%
“…In the present work we also observed high levels of IFN-c synthesis by splenocytes of the RAdEsimmunized mice. This may contribute to the high levels of protection seen in RAdEs-immunized mice as IFN-c production by the T cells was found to be a critical determinant for immune control of JEV infection [58,59].…”
Section: Discussionmentioning
confidence: 99%
“…The increased proliferation of CD4 + T cells in response to live virus compared with inactivated antigen might be because of T-cell responses elicited towards the non-structural proteins of live JEV. Kumar et al (2003) identified the NS3 protein of JEV as a dominant CD4…”
Section: Role Of Cd4mentioning
confidence: 99%